Effect of deformation-induced phase transformation on AISI 316 stainless steel corrosion resistance. (September 2017) - Solomon, Nicolae; Solomon, Iulia
Abstract: Austenitic stainless steels are the mostly used stainless steels in sheet metal forming and are subject of a large variety of applications including plate heat exchangers. During cold plastic deformation of heat exchanger plates, the martensitic transformation can take place. Martensite formation can be considered as a function of temperature, stress or strain. This paper is focused on the influence of martensite transformation on the corrosion resistance of AISI 316 austenitic stainless steel. Corrosion analysis showed that martensitic transformation which occurs due to cold forming process and under cyclic loading conditions had a substantially influence on the corrosion resistance of plate heat exchangers made by AISI 316 austenitic stainless steel. The role of molybdenum in the passive film formation has been considered and it was attributed to the ability of Mo to form insoluble chloride complexes at the base of pits. However, the protective film formed as a result of passivation or repassivation process was continuously broken due to continuously martensitic transformation as a result of cyclic working conditions of plate heat exchanger. The martensite volume expansion continuously broke the passive film and consequently new unprotected surfaces were exposed to chlorine-treated water, which was used as thermal agent for the plate heat exchanger. During working period, the heat exchanger plates are subjected to fluctuating stresses and strains that may result in cracks or fracture after a sufficient number of fluctuations. Fatigue fractures are caused by simultaneous action of cyclic stress, tensile stress and plastic strain. The martensite transformation as a result of applied cold plastic deformation process, changes not only the steel structure, but also its physical and chemical properties. The magnetic properties of stainless steel are very dependent on the elements added into the alloy. Having different corrosion potentials, it is easy for them to become the anode and the cathode, respectively, of a corrosion battery. Highlights: Cyclic loading conditions had a substantially influence on the corrosion resistance of plate heat exchangers. Fatigue fractures are caused by simultaneous action of cyclic stress, tensile stress and plastic strain. Two distinct phases, austenite and martensite which become the anode and the cathode, respectively, of a corrosion battery During martensitic transformation an anodic transient current occurred.